Lipid coating and end functionalization govern the formation and stability of transmembrane carbon nanotube porins - Shen, Chun (2021)
Carbon nanotube (CNT) based transmembrane porins have attracted a lot of recent interest due to their excellent transport properties for water, ions and biomolecules. In experiments, CNTs with a length of about 10 nm can penetrate and form stable transmembrane channels across lipid membranes, while in sharp contrast, similar 10 nm long pristine CNTs were found parallelly clamped inside the hydrophobic core of a lipid bilayer in simulations. This apparent paradox has motivated the present study, where we performed all-atom molecular dynamics simulations to show that lipid molecules initially coated on the CNTs play an essential role in the formation and stabilization of the CNT porins. We demonstrate that, as a lipid coated CNT is inserted into the membrane, lipid molecules arrange themselves into a bicelle on the CNT outside the membrane, providing mechanical support to stabilize the transmembrane configuration of the CNT porin. Further analysis shows that the lipid coating density and end-functionalization strongly influence the CNT insertion into a lipid membrane. These findings shed light on the mechanism of formation and stabilization of CNT porins and provide a theoretical basis to design related transmembrane transport systems.